Design and Test of a 1 DOF Haptic Device for Online Experimentation - Carneiro, Fernando; Quintas, Manuel Rodrigues; Abreu, Paulo; Restivo, Maria Teresa (International Journal of Online and Biomedical Engineering (iJOE), 2016)
This work describes the design and testing of a 1 degree of freedom (DOF) haptic device, for interaction with virtual reality (VR) applications. This device was designed so that it could to be easily assembled by anyone at a reduced price. Instructions for device assembly, as well as some VR appli-cations are available online. The tests performed on the device proved that, despite its low cost, it is able to provide users with a good haptic experience and is adequate for not complex applications.